2016
DOI: 10.3390/nu8100664
|View full text |Cite
|
Sign up to set email alerts
|

Does Human Milk Modulate Body Composition in Late Preterm Infants at Term-Corrected Age?

Abstract: (1) Background: Late preterm infants account for the majority of preterm births and are at risk of altered body composition. Because body composition modulates later health outcomes and human milk is recommended as the normal method for infant feeding, we sought to investigate whether human milk feeding in early life can modulate body composition development in late preterm infants; (2) Methods: Neonatal, anthropometric and feeding data of 284 late preterm infants were collected. Body composition was evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 26 publications
(36 reference statements)
0
17
1
Order By: Relevance
“…Increasing evidence has demonstrated that greater fat-free mass deposition is associated with an improved neurodevelopmental outcome ( 25 ). A study conducted at our center demonstrated that human milk feeding is positively associated with fat-free mass deposition in late preterm infants ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing evidence has demonstrated that greater fat-free mass deposition is associated with an improved neurodevelopmental outcome ( 25 ). A study conducted at our center demonstrated that human milk feeding is positively associated with fat-free mass deposition in late preterm infants ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study on the growth of late preterm infants, we demonstrated that being fed human milk is associated with increased fat-free mass deposition at term corrected age (CA) ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…The impact of a human milk-based diet on the lean and fat mass in late preterm infants was studied by Giannì et al [14]. They found a positive correlation between the consumption of human milk and adipose tissue mass deposition, which strengthens when reaching the term CGA.…”
Section: Human Milk Feeding and Body Composition Parametersmentioning
confidence: 99%
“…skinfold) [ 70 76 ], monitoring growth patterns [ 54 , 77 80 ], investigating the relationship between maternal and prenatal factors and health outcomes during infancy [ 81 86 ], and others [ 87 ]. The majority of these studies ( n = 43) included only full-term infants [ 33 , 52 54 , 56 58 , 60 , 62 , 66 , 67 , 69 72 , 74 , 75 , 78 , 80 , 81 , 83 86 , 88 106 ], 13 only pre-term infants [ 9 , 68 , 73 , 77 , 79 , 107 112 ], and 17 both full- and pre-term infants [ 55 , 59 , 61 , 63 65 , 76 , 82 , 87 , 113 120 ]. Although, the use of Pea Pod in both full-term and pre-term infants and in specific clinical risk and ethnic groups is feasible, it might be associated with some practical challenges.…”
Section: Resultsmentioning
confidence: 99%